Interest appeal of a teacher made course of study - Crouse, Genevieve Lesemann, author; Morgan, David H., advisor; Williamson, Maude, committee member; Morgan, David H., committee member; Elliff, Rowan E., committee member; Hamilton, Olive F., committee member (Colorado State University. Libraries, 1945)
To view the abstract, please see the full text of the document.
Keywords: Home economics -- Study and teaching